Are we really mapping psychosis risk? Neuroanatomical signature of affective disorders in subjects at ultra high risk. Issue 16 (30th April 2014) - Modinos, G.; Allen, P.; Frascarelli, M.; Tognin, S.; Valmaggia, L.; Xenaki, L.; Keedwell, P.; Broome, M.; Valli, I.; Woolley, J.; Stone, J. M.; Mechelli, A.; et al.
Abstract : Background: The majority of people at ultra high risk (UHR) of psychosis also present with co-morbid affective disorders such as depression or anxiety. The neuroanatomical and clinical impact of UHR co-morbidity is unknown. Method: We investigated group differences in grey matter volume using baseline magnetic resonance images from 121 participants in four groups: UHR with depressive or anxiety co-morbidity; UHR alone; major depressive disorder; and healthy controls. The impact of grey matter volume on baseline and longitudinal clinical/functional data was assessed with regression analyses. Results: The UHR-co-morbidity group had lower grey matter volume in the anterior cingulate cortex than the UHR-alone group, with an intermediate effect between controls and patients with major depressive disorder. In the UHR-co-morbidity group, baseline anterior cingulate volume was negatively correlated with baseline suicidality/self-harm and obsessive–compulsive disorder symptoms. Conclusions: Co-morbid depression and anxiety disorders contributed distinctive grey matter volume reductions of the anterior cingulate cortex in people at UHR of psychosis. These volumetric deficits were correlated with baseline measures of depression and anxiety, suggesting that co-morbid depressive and anxiety diagnoses should be carefully considered in future clinical and imaging studies of the psychosis high-risk state.